3D printed biodegradable composites: An insight into mechanical properties of PLA/chitosan scaffold. (September 2020) - Singh, Sunpreet; Singh, Gurminder; Prakash, Chander; Ramakrishna, Seeram; Lamberti, Luciano; Pruncu, Catalin I.
Abstract: Three-dimensional (3D) printing is a frontier manufacturing approach with great potential to benefit biomedical and patient care sectors. In the last decades, different types of biomedical materials were investigated in purpose of developing medical tools and devices. The present study attempts to assess mechanical performances (namely: tensile, compression, and flexural) of the newly developed chitosan-reinforced poly-lactic-acid (PLA) scaffolds by using fused filament fabrication (FFF) based 3D printing technology. Specifically, the effects of chitosan loading, infill density and annealing temperature on mechanical behavior of PLA composite scaffolds are investigated via design of experiments. Moreover, fracture behavior under various load types is studied with the help of selective electron microscopy. It is found that the strength of the produced composite samples depends significantly on the loading of chitosan and infill density, while annealing temperature does not affect mechanical response. Overall, the developed PLA composite scaffolds are mechanically efficient and they appear suitable for clinical purposes. Highlights: Novel chitosan-reinforced PLA scaffold was obtained using fused filamet fabrication. Discontinuities, in polymeric chain, have been indtroduced after the incorporation of chitosan particles. Resulted scaffolds possesed higher mechanical properties ad, therefore, are suitable for dynamic motions.